2019
DOI: 10.3390/en12142837
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Challenges in the Residential Sector: Life Cycle Assessment of Mexican Social Housing

Abstract: Social Housing (SH) in Mexico has a potentially important role in reducing both the emission of greenhouse gases and the use of non-renewable resources, two of the main challenges facing not only Mexico but the planet as a whole. This work assesses the environmental impact generated by the embodied stages of a typical SH throughout its life cycle (cradle to grave), by means of a Life Cycle Assessment (LCA). Two types of envelope and interior walls and three types of windows are compared. It was found that SH e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…Our results validate all six hypotheses and we conclude that bioenergy, RES, energy productivity, urbanization rate, population, and real GDP per capita have a significant impact on CO 2 emission levels in EU countries. These confirm other recent studies [42][43][44][45], which argue that urbanization rates and population are significant factors for CO 2 emission levels.…”
Section: Resultssupporting
confidence: 92%
“…Our results validate all six hypotheses and we conclude that bioenergy, RES, energy productivity, urbanization rate, population, and real GDP per capita have a significant impact on CO 2 emission levels in EU countries. These confirm other recent studies [42][43][44][45], which argue that urbanization rates and population are significant factors for CO 2 emission levels.…”
Section: Resultssupporting
confidence: 92%
“…The multiple regression analysis concluded that the model was valid and correctly specified and the renewables were significant indicators of low carbon levels in all 27 EU countries, since the values of the estimated coefficients of the regression model were significantly different than zero and most of the variation of CO 2 emissions in EU countries was explained by the model. The results of the paper confirm recent studies of renewable energy impact on low carbon levels [47][48][49][50][51][52][53]. In addition, the novelty of this study resides in the fresh outlook taken for a set of 27 EU countries for the period 2008-2017, in order to assess the interaction between renewables and CO 2 emissions.…”
Section: Discussionsupporting
confidence: 79%
“…Very few studies considered the end-of-life phase across LMI countries, and the few that did were not transparent regarding this phase. , As a result, our review does not include the end-of-life phase. Any paper studying energy or emissions from the embodied phase and energy in the use phase of the LCA was considered relevant and included.…”
Section: Synthesis Of Previous Studiesmentioning
confidence: 99%